Factors influencing medication adherence among U.S. Medicare beneficiaries with Alzheimer's disease and related dementia (ADRD). (31st December 2021) - Pilonieta, Giovanna; Pisu, Maria; Martin, Roy C; Shan, Liang; Kennedy, Richard E; Oates, Gabriela; Kim, Young‐Il; Geldmacher, David S
Abstract: Background: For persons with ADRD, access to specialist physicians facilitates appropriate medication use and adherence with treatment. Our objective was to ascertain whether system‐level factors, including availability of specialty physicians predicts ADRD medication adherence among community‐dwelling older adults. Method: We conducted secondary analyses of claims data for Medicare beneficiaries with ADRD in 2013‐2015. Medication adherence was measured using the proportion of days covered (PDC); i.e., ratio of days with ADRD prescriptions over total days of follow‐up. Adherence was defined as PDC >=0.8. Multivariable‐adjusted Modified Poisson regression was used to examine associations of adherence with physicians' availability (defined as number of neurologists and psychiatrist per 1K county population from Area Health Resources File [AHRF]). Analyses adjusted for predisposing factors (sex, race, and age); enabling factors (Medicare/Medicaid dual eligibility, Area Deprivation Index), need factors Alzheimer's disease vs. other) and comorbidities. Context level characteristics from AHRF included county‐level education, urban/rural residence, income/poverty indicator, and mental health professionals shortage area. Because the "Deep South" (DS) region of the US has a shortfall of specialists, we also considered geographic location. Result: We identified 54, 194 Medicare Beneficiaries. The race/ethnicity distribution of the sample was 81.44% white, 9.17 % black, 6.24 % Hispanic, 2.25 % Asian, and 1% other; 71.8 % were female, and 42.36% were >85 years. Bivariate analyses revealed significant differences between DS and non‐DS in all individual and contextual characteristics except sex and comorbidities. Specialists' availability was not significantly associated with adherence to ADRD medication: Neurologists RR: 1.0080, CI (0.9789‐1.0380) and Psychiatrists RR: 1.0066 CI (0.9948‐1.0186). Age, dual eligibility, and living in non‐large metropolitan areas were associated with a higher probability of adherence. Race, comorbidities, having ≥1 visit with specialists, and context factors such as living in deprived and lower education areas were associated with a lower probability of adherence. Conclusion: Adherence to ADRD medications was not associated with specialist availability but was related to individual and socioeconomic context factors in community‐dwelling older individuals with ADRD. Research should continue ascertaining factors that may influence medication adherence, particularly communities with a higher prevalence of ADRD risk factors, a greater proportion of minorities and socially at‐risk people, and health disparities.